Interest Theory–Supply and Demand for Loans or Supply and Demand for Cash: Comment on Dr. Lerner's Note - Fellner, William J.; Somers, Harold M. (The Review of Economics and Statistics, 1944)
William J. Fellner, Harold M. Somers, Interest Theory–Supply and Demand for Loans or Supply and Demand for Cash: Comment on Dr. Lerner's Note, The Review of Economics and Statistics, Vol. 26, No. 2 (May, 1944), p. 92